A comprehensive analysis of the velocity-based method in the shoulder press exercise: stability of the load-velocity relationship and sticking region parameters - Hernández-Belmonte, Alejandro; Martínez-Cava, Alejandro; Morán-Navarro, Ricardo; Courel-Ibáñez, Javier; Pallarés, Jesús (Biology of Sport, 2021)
The purpose of this study was threefold: i) to analyse the load-velocity relationship of the shoulder press (SP) exercise, ii) to investigate the stability (intra-individual variability) of this load-velocity relationship for athletes with different relative strength levels, and after a 10-week velocity-based resistance training (VBT), and iii) to describe the velocity-time pattern of the SP: first peak velocity [V max1 ], minimum velocity [V min ], and second peak velocity [V max2 ]. This study involves a cross-sectional (T1, n = 48 subjects with low, medium and high strength levels) and longitudinal (T2, n = 24 subjects randomly selected from T1 sample) design. In T1, subjects completed a progressive loading test up to the 1RM in the SP exercise. The barbell mean, peak and mean propulsive velocities (MV, PV and MPV) were monitored. In T2, subjects repeated the loading test after 10 weeks of VBT. There were very close relationships between the %1RM and velocity attained in the three velocity outcomes (T1, R2 : MV = 0.970; MPV = 0.969; PV = 0.954), being even stronger at the individual level (T1, R2 = 0.973–0.997). The MPV attained at the 1RM (~0.19 m·s-1) was consistent among different strength levels. Despite the fact that 1RM increased ~17.5% after the VBT programme, average MPV along the load-velocity relationship remained unaltered between T1 and T2 (0.69 ± 0.06 vs. 0.70 ± 0.06 m·s-1). Lastly, the three key parameters of the velocity-time curve were detected from loads > 74.9% 1RM at 14.3% (V max1 ), 46.1% (V min ), and 88.7% (V max2 ) of the concentric phase. These results may serve as a practical guideline to effectively implement the velocity-based method in the SP exercise.